Osteonecrosis of the jaw associated with intravenous administration of bisphosphonates in palliative home care – a case report - Kluczna, Agnieszka; Jamka-Kasprzyk, Małgorzata; Dzierżanowski, Tomasz (Medycyna Paliatywna/Palliative Medicine, 2020)
Osteonecrosis of the jaw is an uncommon side effect of bisphosphonates that are used in patients with bone metastases. The paper presents a case of a patient with breast cancer and numerous bone metastases, who received an intravenous infusion of zoledronic acid every 28 days for 4.5 years. The indication for the administration of bisphosphonates was the prevention of bone complications. The patient was diagnosed with osteonecrosis of the jaw associated with the administration of zoledronic acid and underwent surgical treatment. In this article, we pointed out the necessity of sanitation of the oral cavity before administration of oncological doses of bisphosphonates, repeated dentist control, and self-examination of teeth condition during the bisphosphonate treatment, as well as reduction of risk factors, in order to prevent osteonecrosis of the jaw.